2018
DOI: 10.3390/molecules23102544
|View full text |Cite|
|
Sign up to set email alerts
|

Intestinal Saturated Long-Chain Fatty Acid, Glucose and Fructose Transporters and Their Inhibition by Natural Plant Extracts in Caco-2 Cells

Abstract: The intestinal absorption of fatty acids, glucose and fructose is part of the basic requirements for the provision of energy in the body. High access of saturated long-chain fatty acids (LCFA), glucose and fructose can facilitate the development of metabolic diseases, particularly the metabolic syndrome and type-2 diabetes mellitus (T2DM). Research has been done to find substances which decelerate or inhibit intestinal resorption of these specific food components. Promising targets are the inhibition of intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 168 publications
(244 reference statements)
0
22
0
Order By: Relevance
“…Screening a few ratios of CPT:PTX showed 5.22:1 to be most effective in cytotoxicity assays in vitro . We performed these assays using Caco-2 cells, which are heterogeneous human epithelial colorectal adenocarcinoma cells (Schreck and Melzig, 2018) used most often as a confluent monolayer rather than individual cells (Ellens et al, 2018); the monolayer can, under certain conditions, form a polarized epithelial cell monolayer (Gibaud and Attivi, 2012). Therefore Caco-2 was used here to mimic normal colorectal epithelial cells (Beloqui et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Screening a few ratios of CPT:PTX showed 5.22:1 to be most effective in cytotoxicity assays in vitro . We performed these assays using Caco-2 cells, which are heterogeneous human epithelial colorectal adenocarcinoma cells (Schreck and Melzig, 2018) used most often as a confluent monolayer rather than individual cells (Ellens et al, 2018); the monolayer can, under certain conditions, form a polarized epithelial cell monolayer (Gibaud and Attivi, 2012). Therefore Caco-2 was used here to mimic normal colorectal epithelial cells (Beloqui et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Since polyphenols obtained from dietary sources gain high concentration in gut lumen, they are able to regulate biological activities of the cells in the intestine. Recent data proved that polyphenols are able to influence intestinal processes of glucose and FFA absorption, not only via inhibition of digestive enzymes, but also by attenuation of their uptake [10,11,12]. Some investigations suggested that polyphenolic compounds lower glucose absorption via influence on the sodium-dependent glucose transporter 1 (SGLT1), however, their stronger inhibition potential was identified in the case of the sodium-free glucose transporter known as GLUT2 [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, literature data showed the ability of a large variety of classes of dietary polyphenols, including rutin, quercetin, myricetin, ellagic acid [ 30 ], and avicularin [ 38 ], all present in our extract, to affect glucose transport in Caco-2 cells via both facilitated transport proteins (GLUT 1 and 2) and sodium-dependent glucose transporter 1 (SGLT1). Several natural extracts, usually rich in these molecules, were also found to inhibit glucose uptake in Caco-2 cells through these mechanisms [ 38 , 71 ]. Being the main cellular energetic source, glucose plays a key role also in cancer cell growth [ 72 ].…”
Section: Discussionmentioning
confidence: 99%